Unaltered maximal power and submaximal performance correlates with an oxidative vastus lateralis proteome phenotype during tapering in male cyclists - Pieter deLange; Giuseppe Petito; Hannah L. Notbohm; Antonia Giacco; Giovanni Renzone; Elena Silvestri; Arianna Cuomo; Frank Suhr; Thorsten Schiffer; Jonas Zacher; Federica Cioffi; Rosalba Senese; et al. (Physiological Reports)
Abstract Little is known on how a short‐term reduction of training volume changes muscle proteome and physiological parameters. We investigated the impact of halving training volume during regular training of cyclists on physiological parameters in relation to vastus lateralis protein profiles and fiber percentage ratios. Fifteen male cyclists (age: 30.1 ± 9.6 yrs.; VO2max: 59.4 ± 4.4 mL∙kg−1∙min−1; weekly training volume: 8.7 ± 2.3 h) participated in an 11‐week training intervention. During 2 weeks after a shared training programme for 9 weeks, a control group continued training and a taper group reduced training volume by 50%. No end‐point differences were found for peak power output, maximal oxygen uptake, or peak and mean power in a sprint test (p > 0.05), although in the taper group, muscle proteins involved in mitochondrial aerobic respiration increased whereas those involved in translation, protein catabolism, and actin organization decreased, without between‐group differences in type I/type II fiber percentage ratios. Tapering did not decrease power at the first (LT1) and second lactate threshold (LT2) compared to t0, whereas power increased in the control group (LT1: 216 ± 28 W vs. 238 ± 11 W, p = 0.042, LT2: 290 ± 42 W vs. 318 ± 13 W, p = 0.005). Our data indicate that transient 50% training volume reductions may be beneficial for oxidative metabolism in muscle.